Manajemen Laba, Leverage Dan Penghindaran Pajak: Peran Moderasi Tanggung Jawab Sosial Perusahaan - David Manuel; Sandi Sandi; Amrie Firmansyah; Estralita Trisnawati (Politeknik Keuangan Negara STAN, 2022)
This study aims to examine the effect of earnings management and leverage on tax avoidance where this study is also to examine the moderating role of corporate social responsibility in the relationship between earnings management and leverage on tax avoidance. The sample in this study are various industrial sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2018-2020. From the results of purposive sampling, the number of samples used in this study were 36 observations. In this study, the data were processed using a panel data model. Hypothesis testing using multiple linear regression analysis. This study shows that earnings management has an effect on tax avoidance while Leverage has no effect on tax avoidance. In addition, this study finds that corporate social responsibility cannot moderate the effect of earnings management on tax avoidance and weakens the effect of leverage on tax avoidance.